1990
DOI: 10.3109/00952999009001573
|View full text |Cite
|
Sign up to set email alerts
|

“Hello, May We Help You?” A Study of Attrition Prevention at the Time of the First Phone Contact with Substance-Abusing Clients

Abstract: The problem of early attrition from treatment is pervasive throughout community mental health and is particularly high for substance-abusing clients. In spite of the severity of this problem and the potential for successful interventions, there have not been many studies that attempt to reduce the dropout rate of drug abusers. The purpose of this research was to test the effectiveness of attrition prevention procedures at the time of the client's first phone contact with the clinic. Callers were either given a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 19 publications
5
40
0
Order By: Relevance
“…The likelihood of treatment-seeking substance abusers actually entering treatment after assessment is often <50% (Donovan, Rosengren, Downey, Cox, & Sloan, 2001;Stark, Campbell, & Brinkerhoff, 1990). In part, this is related to substance abusers' limited tolerance for treatment wait time, with longer waits associated with higher rates of pretreatment attrition (Festinger, Lamb, Kountz, Kirby, & Marlowe, 1995;Hser, Maglione, Polinsky, & Anglin, 1998;Kaplan & Johri, 2000).…”
Section: Impact Of Waiting Timementioning
confidence: 99%
“…The likelihood of treatment-seeking substance abusers actually entering treatment after assessment is often <50% (Donovan, Rosengren, Downey, Cox, & Sloan, 2001;Stark, Campbell, & Brinkerhoff, 1990). In part, this is related to substance abusers' limited tolerance for treatment wait time, with longer waits associated with higher rates of pretreatment attrition (Festinger, Lamb, Kountz, Kirby, & Marlowe, 1995;Hser, Maglione, Polinsky, & Anglin, 1998;Kaplan & Johri, 2000).…”
Section: Impact Of Waiting Timementioning
confidence: 99%
“…D'autres chercheurs (Bell, 1985;Craig, 1985;De Leon, Melnick, Kressel, Jainchill, 1994;Keso & Salaspuro, 1990 ;Stark, Campbell & Brinkerhoff, 1990;Stark, 1992) (Bergeron & al., 2000).…”
Section: Les Déterminants De La Persévérance Au Traitement Bergeronmentioning
confidence: 99%
“…However, in North America waiting lists for substance use treatment experience a 50% attrition rate. [1][2][3][4][5] Kaplan and Johri (2000) found that the average tolerance for waiting for treatment is one month, and that 40% of substance users will drop from a waiting list within the first two weeks of being on one. 6 According to the Center for Substance Abuse Treatment approximately one million people are waiting for publicly funded treatment.…”
Section: Introductionmentioning
confidence: 99%